Comparative associations of body mass index and waist-to-height ratio with cardiometabolic and functional health risk markers in children aged 6–12 years - the Health Oriented Pedagogical Project (HOPP) - Per Morten Fredriksen; Morten Lindberg; Nandu Goswami; Asgeir Mamen (PLoS ONE, 2026)
Background Body mass index (BMI) and waist-to-height ratio (WHtR) are widely used markers of adiposity in children, but their relative associations with cardiometabolic and functional health measures remain debated. Methods We analyzed data from children aged 6–12 years (n = 2297) in the Health Oriented Pedagogical Project (HOPP) with annual assessments from 2015–2020. Associations between BMI or WHtR and outcomes (body composition, blood lipids, blood pressure, physical activity, and cardiorespiratory fitness/endurance) were examined using linear mixed-effects models with repeated measures (random intercept for child; study year as the repeated factor). BMI and WHtR were evaluated in separate models. Results Both BMI and WHtR were consistently associated with less favorable profiles across outcomes, including higher adiposity, lower fitness/endurance and MVPA, higher blood pressure, and a more adverse lipid profile (lower HDL and higher non-HDL cholesterol). Across most outcomes, differences between BMI- and WHtR-based models were modest; however, WHtR generally showed slightly stronger associations for lipid measures and fitness-related outcomes. Conclusions BMI and WHtR demonstrate largely comparable associations with cardiometabolic and functional health measures in children aged 6–12 years. WHtR may provide complementary information on central adiposity and can be considered alongside BMI in pediatric screening and surveillance.